Exploring CSR Strategies and Their Impact on Brand Awareness: A Case Study of Toko Kopi Sedaya - Alvian, Rivaldy Dwi; Sumarlan, Iman (Golden Ratio of Marketing and Applied Psychology of Business, 2025)
In today's highly competitive business landscape, Corporate Social Responsibility (CSR) has emerged as a key strategy for building public trust and enhancing brand awareness, especially among small and medium enterprises (SMEs). To understand how social initiatives contribute to strengthening brand identity, this study explores the CSR strategies implemented by Toko Kopi Sedaya, a local coffee shop in Yogyakarta. Using a qualitative descriptive approach, the research involved in-depth interviews, observations, and analysis of social media content to examine the planning, implementation, and impact of CSR programs. The findings reveal that Toko Kopi Sedaya integrates CSR activities such as barista training for local youth, sourcing from local farmers, and community engagement programs into its brand communication strategy. These efforts significantly contribute to brand recognition, emotional consumer connection, and customer loyalty. The study highlights that when strategically aligned with brand values and communicated effectively, CSR can be a powerful tool for enhancing brand awareness and building a sustainable business identity. This research contributes to the theoretical understanding of CSR's role in strategic brand development within the context of SMEs.